CD94 as a novel marker for immunophenotyping of leukemia and lymphoma in dogs - Blockeel, Anna; Demeyere, Kristel; Steenbrugge, Jonas; Paepe, Dominique; Krupa, Adriana; Martini, Valeria; Devriendt, Bert; Meyer, Evelyne (Frontiers in Veterinary Science, 2025)
CD94 is a natural killer (NK) cell receptor that also marks subsets of T cells, referred to as NKT cells. In humans, the role of CD94 as both an immune checkpoint and a potential therapeutic target has gained increasing attention. However, data about its expression in leukemia and lymphoma in dogs remain limited. This study aimed to explore CD94 expression in canine leukemia and nodal lymphoma, using a newly available anti-canine CD94 monoclonal antibody in a multicolor flow cytometry panel. Surplus blood and lymph node aspirate samples from eleven client-owned dogs (leukemia: n = 7, lymphoma n = 4) and two clinically healthy controls, were analyzed. The control dogs as well as most cases showed low CD94+ lymphocyte frequencies, consistent with a non-neoplastic population. However, markedly expanded CD94+ populations were identified in two out of four of the T cell chronic lymphocytic leukemia (T-CLL) cases. In one of them, the neoplastic population was uniformly CD3+CD8+CD94+, while the other showed a heterogeneous mixture of CD3+CD8+CD94+ and CD3−CD8+CD94+ lymphocytes. Our findings demonstrate that the canine-specific CD94 antibody can be applied to both blood and lymph node samples in a diagnostic flow cytometry setting. While CD94 expression was infrequent overall, its detection in a subset of T-CLL cases highlights the need for larger studies to determine its diagnostic and therapeutic value in canine leukemia and lymphoma.